5*x-7=-6*x-29

Simple and best practice solution for 5*x-7=-6*x-29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5*x-7=-6*x-29 equation:


Simplifying
5x + -7 = -6x + -29

Reorder the terms:
-7 + 5x = -6x + -29

Reorder the terms:
-7 + 5x = -29 + -6x

Solving
-7 + 5x = -29 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-7 + 5x + 6x = -29 + -6x + 6x

Combine like terms: 5x + 6x = 11x
-7 + 11x = -29 + -6x + 6x

Combine like terms: -6x + 6x = 0
-7 + 11x = -29 + 0
-7 + 11x = -29

Add '7' to each side of the equation.
-7 + 7 + 11x = -29 + 7

Combine like terms: -7 + 7 = 0
0 + 11x = -29 + 7
11x = -29 + 7

Combine like terms: -29 + 7 = -22
11x = -22

Divide each side by '11'.
x = -2

Simplifying
x = -2

See similar equations:

| 10=b(5) | | 3p=5 | | b-1=-9 | | 180=115+x+x | | X-3/5x | | 2x+8+6x-4=84 | | 7=3y-17 | | 6x-(4x-32)=0 | | 125m-100m+43,650=45,675-300m | | (16x-3)(4)=0x | | 4(6p-3)=-39-3p | | -.4*p+2=.2*p+11 | | (16x-3)(4)=0 | | 10x-6=7x | | y+(-10)=36 | | 8y+1=2y-26 | | .5f+10=48 | | 6(2x+3)+2= | | (16x-3)(2)=0 | | 8p+9p=34 | | a-6-7a=1-6a | | 11c-4-3=8 | | (16x-3)(8)=0 | | 1/3x-1/6y=1 | | -4/5a=12/17 | | 2x-6=8-2x | | 3=2y | | 16x+3=47 | | 4+17/-2=0 | | 8(2a-8)=-4(-3a+6) | | 2c+c+12=14 | | 1/2f+10=48 |

Equations solver categories